Porosity development in activated carbon from palm kernel and coconut shell by chemical activation method - Md. Mokhlesur , Rahman; Adil, Mohammad; Yusof, Alias Mohd (2011)
A preparation and modification of activated carbon from oil-palm shell has been investigated in this paper. A pretreatment method has been established to avoid partial fusion and swelling in the carbonization stage. Carbonization has been studied at different temperatures and the structure of the microporous chars has been characterized. Activated carbon has been prepared from steam gasification of chars obtained at 800O C. This activation increases both total and narrow microporosity and develops a substantial mesoporosity. Activated carbon with different pore size distribution is impregnated with zirconium chloride and iron chloride salts to give impregnated carbon with different metals loading. The presences of active metal on an impregnated activated carbon surface greatly affect the adsorption affinity since some inorganic compounds will then be adsorbed preferentially.